An image of harmony - Rúpar, Marilyn (s.n., 1987)
An illustrated account of Cataldo Mission, Idaho, its influence on the Coeur d'Alene Indians and the surrounding region, including a brief history of Rev. Anthony Ravalli, S.J., who founded the Mission in ca. 1850.